2011
DOI: 10.1245/s10434-011-2038-z
|View full text |Cite
|
Sign up to set email alerts
|

Is Intraoperative Imprint Cytology Evaluation Still Feasible for the Evaluation of Sentinel Lymph Nodes for Lobular Carcinoma of the Breast?

Abstract: Background The evaluation of sentinel lymph nodes (SLNs) from a patient with lobular breast cancer is challenging. Metastatic lobular cancer is difficult to identify in SLNs because of its low-grade cytomorphology and its tendency to resemble lymphocytes. Intraoperative imprint cytology (IIC) is a rapid, reliable method for evaluating SLNs intraoperatively. We sought to reexamine our experience with this technique in the identification of invasive lobular breast cancer SLN metastases. Methods A retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…We do not notice any significant difference in the sensitivity ( P values = .9470) and specificity ( P values = .6709) of ISC for lobular/ducto‐lobular and other cytotypes, in agreement with the findings of Creager et al and Howard‐McNatt et al regarding touch imprints and of Horvath et al and Taras et al about frozen sections. Furthermore, lack of differences in sensitivity and specificity between chemotherapy‐naive patients and patients receiving neoadjuvant chemotherapy demonstrates that the techniques we are discussing are additionally useful in this setting; however, the literature is not concordant on the use of SLNB in chemotherapy‐treated patients, with some authors in favor and others not in favor …”
Section: Discussionsupporting
confidence: 91%
“…We do not notice any significant difference in the sensitivity ( P values = .9470) and specificity ( P values = .6709) of ISC for lobular/ducto‐lobular and other cytotypes, in agreement with the findings of Creager et al and Howard‐McNatt et al regarding touch imprints and of Horvath et al and Taras et al about frozen sections. Furthermore, lack of differences in sensitivity and specificity between chemotherapy‐naive patients and patients receiving neoadjuvant chemotherapy demonstrates that the techniques we are discussing are additionally useful in this setting; however, the literature is not concordant on the use of SLNB in chemotherapy‐treated patients, with some authors in favor and others not in favor …”
Section: Discussionsupporting
confidence: 91%
“…The use of transgenic mouse line with fluorescent protein-labeled is another sophisticated methodology [35]. The imprinting is a simple methodology, routinely used for diagnostic in other situations, as in the evaluation of sentinel lymph nodes for lobular carcinoma of the breast cancer [36]. Several studies have demonstrated that the imprinting is superior to freezing, particularly in cases where the preservation of the tissue structure is not required [37-40].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a higher probability of false-negative results has been recorded and the presence of micrometastasis cannot be excluded 1113. Sensitivity also depends on the histologic type of the tumor, with lower rates of detection for lobular carcinoma (LC) in comparison with the more common ductal type 14,15. Additional immunohistochemical staining may aid in the detection of micrometastases even in LC and contributes to the increase of IC sensitivity 16.…”
Section: Introductionmentioning
confidence: 99%